TINJAUAN EKONOMI PROVINSI RIAU - Wawan Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
Riau Province is one of the most faster income per capita growth in sumatera lslands. The economic base of economic structure in Riau Province is Forestry sector. This leading sector improve government income through Local tax income. This phenomenon